2002
DOI: 10.1124/dmd.30.5.582
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of Budesonide by Human Cytosolic Sulfotransferase, Dehydroepiandrosterone-Sulfotransferase (DHEA-ST)

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Budesonide, a synthetic glucocorticosteroid, is used in the treatment of asthma and allergic reactions, rhinitis, and inflammatory bowel disease. It is distributed as a mixture of two epimers, 22R and 22S, and has a high ratio of topical to systemic activity due to extensive first-pass metabolism to metabolites with minimal activity. Previous studies have shown that the epimers are metabolized by the cytochrome P450 monooxygenase system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…The plates were developed in methylene chloride:MeOH:ammonium hydroxide (85:15:5 by volume) and the radiolabeled sulfated products were localized by autoradiography. The sulfated products were scraped into scintillation fluid and radioactivity was determined by scintillation spectroscopy (16,21,30). Significant differences between reactions with and without STS was determined using the Students T-test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The plates were developed in methylene chloride:MeOH:ammonium hydroxide (85:15:5 by volume) and the radiolabeled sulfated products were localized by autoradiography. The sulfated products were scraped into scintillation fluid and radioactivity was determined by scintillation spectroscopy (16,21,30). Significant differences between reactions with and without STS was determined using the Students T-test.…”
Section: Methodsmentioning
confidence: 99%
“…Raloxifene is sulfated in vitro by at least seven expressed human SULT isoforms including SULTs 1E1 and 2A1 (12,17). SULT1E1 is responsible for the high affinity sulfation of estrogens (14,18,19) while SULT2A1 sulfates hydroxysteroids, bile acids and several therapeutic drugs (10,15,20,21). SULT1E1 and SULT2A1 are also of interest since SULT1E1 can form raloxifene disulfate and SULT2A1 can generate the 3-OH Tib disulfates (10,12).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of these metabolites is less than 1% of that of the parent compound, and they do not contribute further to the therapeutic effect of budesonide (Silverman & Otley, 2011). In vitro studies of the phase II metabolism of budesonide have demonstrated that it undergoes sulfation by cytosolic sulfotransferase enzyme 1A1 (Meloche et al, 2002); studies in lung tissue slices have also demonstrated the formation of fatty acid esters from budesonide (Nave et al, 2007). Budesonide is eliminated in the urine (60%) and faeces (40%) as metabolites (US Food and Drug Administration, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is rapidly and almost completely absorbed from the gastrointestinal tract, its bioavailability is low (about 10%) due to extensive first-pass metabolism in the liver. Furthermore, the metabolites produce less than 1% of the glucocorticoid activity when compared to the unchanged budesonide 1,2 . As with other glucocorticosteroids, long-term administration of systemic budesonide may cause many adverse effects such as hypothalamic-pituitary-adrenal suppression, growth retardation, and osteoporosis 3 .…”
Section: Introductionmentioning
confidence: 99%